2019
DOI: 10.1007/s12253-019-00705-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Characteristics of Glioblastoma in Genome-Wide Studies

Abstract: Glioblastoma is one of the deadliest tumors with barely over one-year median survival despite intensive efforts in defining its molecular characteristics and searching for innovative treatment strategies. While major progress has been made in cataloging cross-sectional genomic, transcriptomic and epigenomic features of the tumor, and inferring its main molecular pathways and niches for potential targeted intervention, we still do not have sufficient knowledge concerning evolutionary patterns and dynamics of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…While the molecular profiles of primary GBMs have been extensively studied (Brennan et al, 2013;Ceccarelli et al, 2016;Johnson et al, 2018), ultimately most patients succumb to recurrent disease. Given that recurrent tumors are often genetically and transcriptionally distinct from their primary tumors (Kraboth and Kalman, 2020), a better understanding of the molecular underpinnings of recurrent disease is crucial to improving outcomes for GBM. Two main factors make the study of recurrent GBM tumors particularly difficult: (1) only $25% of patients are eligible for repeat surgery upon recurrence (Weller et al, 2013), and (2) even resectable recurrent tumors tend to have a higher rate of necrosis, which can make molecular profiling difficult or impossible (Marucci et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While the molecular profiles of primary GBMs have been extensively studied (Brennan et al, 2013;Ceccarelli et al, 2016;Johnson et al, 2018), ultimately most patients succumb to recurrent disease. Given that recurrent tumors are often genetically and transcriptionally distinct from their primary tumors (Kraboth and Kalman, 2020), a better understanding of the molecular underpinnings of recurrent disease is crucial to improving outcomes for GBM. Two main factors make the study of recurrent GBM tumors particularly difficult: (1) only $25% of patients are eligible for repeat surgery upon recurrence (Weller et al, 2013), and (2) even resectable recurrent tumors tend to have a higher rate of necrosis, which can make molecular profiling difficult or impossible (Marucci et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed the overexpression of NANOS3 in glioblastoma cell lines and tissues. Glioblastoma is the most common type of brain cancer that is characterized by high heterogeneity, mortality, and short median survival rate [ 39 ]. Moreover, molecular mechanisms leading to glioblastoma are not well understood.…”
Section: Nanos3 In Cancermentioning
confidence: 99%
“…Some studies speculate that distant recurrence 5 -10 years after the first operation is actually a new primary tumor; these tumors grow independently and may be caused by adjuvant radiotherapy or chemotherapy [26] [27]. However, other studies have found sufficient genetic similarity between distant recurrent tumors and primary tumors, suggesting that distant recurrent tumors are distant recurrence of primary tumors rather than independent primary GBM [28].…”
Section: Recurrent Glioblastomamentioning
confidence: 99%